A Best Practice of Water Management at Mahidol University, Salaya Campus, Thailand - Kitikorn Charmondusit; Sasivimon Pungpermtrakul; Banchong Mahisavariya (Journal of Sustainability Perspectives, 2021)
Mahidol University is one of the most environmentally friendly university in Thailand. The eco-university policy for sustainable development on campus and in the surrounding community has been implemented in order to balance of economic, social and environmental dimensions which will lead to efficient use of resources, social equality and improved quality of life of staff, students and the surrounding community. Water management of MU, Salaya campus is one of the successful case studies. Approximately 60% of the 1,867,792 square meters of campus was allocated for the green and water reservation areas including horizontal garden, vertical garden, botanic garden, original wetland, ditch and pond. The RINGLOOP project was installed in order to improve the performance of water distribution. The central wastewater treatment plant with activated sludge system has been constructed. The water conservation program with 100% of treated wastewater recyclable is implemented